Research of Slope Shift Strategy for Vehicle Automatic Transmission based on Slope and Vehicle Mass Identification - Xia Guang; Tu Botao; Tang Xiwen; Sun Baoqun (Jixie chuandong)
The slope and vehicle mass are identified in real time by using the variable forgetting factor least square method which have strong adaptability and good following performance. On this basis,the slope shift hierarchical modification control of vehicle automatic transmission is carried out,the gearshift process of vehicle automatic transmission is divided into the upper identification decision layer and the lower shift executive layer. Through the upper decision-making layer acquisition vehicle sensor signal parameters,the slope and vehicle mass identification,the slope shift modification control decision are carried out. The lower shift executive layer receive the correction control instruction from upper identification decision layer to complete gear shift correction execution. The results of simulation and hardware-in-the-loop test show that,the slope and vehicle mass can be accurately identified by using variable forgetting factor least square method,the slope shift hierarchical modification control strategy can solve the frequent shift and unexpected shift phenomenon and reducing the wear of gear shifting parts. On other hand vehicle could full use of the engine braking torque characteristics,reduce the wear of braking system when downhill slopes.